Analysis of Service Quality, Promotion, and Facilities on Customer Satisfaction - Kurnia Nur Hudzaifah; Yuniman Zebua; Bhakti Helvi Rambe (Almana : Jurnal Manajemen dan Bisnis, 2023)
Consumer satisfaction has an important role as a determinant for the success and development of a culinary company. So, the company must be able to make consumers feel satisfied and become loyal customers. There are several influencing factors, namely regarding the quality of service, promotion, and facilities that must be provided. This study aims to analyze the influence of the variables of service quality, promotion, and facilities on customer satisfaction. This study uses a quantitative research method, in which this method uses measurement tools or applications to obtain statistical values. The research population is customers who have visited the Ayam Penyet Cindelaras Rantauperapat Restaurant. The data that has been collected and obtained from the results of this study is then calculated using the smart plus 4 applications. From the results of the calculations that have been obtained, it is concluded that all outer loading values for each indicator are declared valid because they meet the standard or have an AVE value greater than 0.5 (> 0.5). latent variable consumer satisfaction has a good R Square value because it has a value greater than 0.75. Therefore, it can be concluded that the diversity of service quality variables, promotions, and facilities can affect the consumer satisfaction variable by 93%.